2014
DOI: 10.13102/sociobiology.v59i1.676
|View full text |Cite
|
Sign up to set email alerts
|

Do Tunnel Patterns of Coptotermes formosanus and Coptotermes gestroi (Blattodea: Rhinotermitidae) Reflect Different Foraging Strategies?

Abstract: Tunnel network construction and time to food (wood) discovery by Coptotermes formosanus Shiraki and Coptotermes gestroi (Wasmann) (Blattodea: Rhinotermitidae) (formerly known as Coptotermes vastator Light in the Pacific region) was examined when wood was present in a clumped distribution that mimics field conditions in the subtropical and temperate regions where C. formosanus naturally occurs. Previous research has noted that the tropical species C. gestroi constructs a highly branched tunnel network, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
(22 reference statements)
2
6
2
Order By: Relevance
“…Even if the two termite species did not differ in the time taken to find the first piece of wood, which was possible since the arenas were fairly small, the longer and straighter tunnels constructed by C. formosanus would be expected to give it an advantage in discovering the second piece of wood at the opposite end of the arena, since C. gestroi would be expected to construct a dense network of tunnels around the first piece of wood discovered rather than immediately striking out across the arena. As predicted, C. formosanus did indeed locate the first piece of wood in the arenas an average of one day faster than C. gestroi (2.5 vs. 3.5 days), and then discovered the second piece of wood at the opposite end of the arena an average of 2.5 days faster as well (6 vs. 8.5 days) (Hapukotuwa and Grace 2012c). Yeoh and Lee (2007) also observed that the dense and heavily branched tunneling networks of C. gestroi and C. curvignathus Homgren contrasted with the straight and relatively unbranched tunnels of C. kalshoveni Kemner.…”
Section: Bt Forschler (Ed) Proceedings Of the 10th Pacific-rim Termsupporting
confidence: 71%
“…Even if the two termite species did not differ in the time taken to find the first piece of wood, which was possible since the arenas were fairly small, the longer and straighter tunnels constructed by C. formosanus would be expected to give it an advantage in discovering the second piece of wood at the opposite end of the arena, since C. gestroi would be expected to construct a dense network of tunnels around the first piece of wood discovered rather than immediately striking out across the arena. As predicted, C. formosanus did indeed locate the first piece of wood in the arenas an average of one day faster than C. gestroi (2.5 vs. 3.5 days), and then discovered the second piece of wood at the opposite end of the arena an average of 2.5 days faster as well (6 vs. 8.5 days) (Hapukotuwa and Grace 2012c). Yeoh and Lee (2007) also observed that the dense and heavily branched tunneling networks of C. gestroi and C. curvignathus Homgren contrasted with the straight and relatively unbranched tunnels of C. kalshoveni Kemner.…”
Section: Bt Forschler (Ed) Proceedings Of the 10th Pacific-rim Termsupporting
confidence: 71%
“…Nevertheless, in the present study, the multiple-choice tests showed that H. tenuis and C. gestroi display the same behavioral patterns in relation to the consumption and the recruitment of foragers for equivalent food sources, and these facts suggest that subterranean termites did not concentrate their efforts on the consumption of only one food when multiple resources are available. Hapukotuwa & Grace (2012) verified that C. gestroi continues to shift from one food source to another, rather than remaining until each food resource is consumed, confirming the idea that this species does not display a chronological priority in relation to the location of food.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, C. formosanus colonies built shorter and wider primary tunnels compared to R. flavipes [ 48 ]. It is proposed that the differences in foraging strategy are partly dependent on resource abundance in the native range of the species, with longer and less branched tunnels associated with clumped and heterogeneous resources, and short and highly branched tunnels efficient for locating homogenously distributed resources [ 49 ]. The ecological drivers of different foraging strategies require further investigation in subterranean termite species.…”
Section: Discussionmentioning
confidence: 99%